2020
DOI: 10.3390/ijerph17228611
|View full text |Cite
|
Sign up to set email alerts
|

Can Healthy Checkout Counters Improve Food Purchases? Two Real-Life Experiments in Dutch Supermarkets

Abstract: Most snacks displayed at supermarket checkouts do not contribute to a healthy diet. We investigated the effects of introducing healthier snack alternatives at checkouts in supermarkets on purchasing behavior. In Study 1, we investigated the effect of completely substituting less healthy with healthier snacks (one supermarket). In Study 2, we investigated the effect of placing and discounting healthier snacks while the less healthy snacks remain in place (two supermarkets). In both studies, the number of purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The increase in micro-pack sales in group 1 stores remained significantly higher than the pre-intervention period during the second phase of the intervention, demonstrating a sustained effect of the intervention in those stores. These results are similar to other studies that have examined the impact of healthy checkout interventions, which found that healthy purchases increased during the intervention period (21,(29)(30)(31)(32)(33)(34)(35) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increase in micro-pack sales in group 1 stores remained significantly higher than the pre-intervention period during the second phase of the intervention, demonstrating a sustained effect of the intervention in those stores. These results are similar to other studies that have examined the impact of healthy checkout interventions, which found that healthy purchases increased during the intervention period (21,(29)(30)(31)(32)(33)(34)(35) .…”
Section: Discussionsupporting
confidence: 90%
“…Interventions have ranged in duration from 4 d to 6 months, substituting unhealthy items like candy and soda with fresh fruits and vegetables, dried fruit, cereal bars, nuts, dried fish and bottled water or removing unhealthy items altogether. Five studies added healthy items to checkout aisles and found that sales of healthier items increased (21,(29)(30)(31) , but there was no reduction in the sales of less healthy items (29)(30)(31) . Three studies substituted unhealthy foods with healthier options at checkout aisles and reported mixed results.…”
mentioning
confidence: 99%
“…One study carried out in the United States found that more healthy items were purchased from the checkout only offering healthy foods compared with the standard checkout, but purchasing was generally low (Adjoian et al, 2017). Another study which used a pre‐post design, in The Netherlands, found that the total number of snacks sold was 2.4 times lower when all less healthy foods were removed and replaced with healthier options (Huitink, Poelman, Seidell, Kuijper, Hoekstsra, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, experimental studies manipulating the availability of snack foods at supermarket checkouts have had mixed findings. Some studies have found limited impact on purchasing of less healthy foods (Huitink, Poelman, Seidell, Pleus et al, 2020; Winkler et al, 2016), while others found reduced sales of less healthy foods (Sigurdsson et al, 2014), a decrease in absolute number of snack foods purchased (Huitink, Poelman, Seidell, Kuijper, et al, 2020) or an increase in healthier foods purchased (Adjoian et al, 2017; Payne & Niculescu, 2018; Sigurdsson et al, 2014). In a different setting, sales data from a hospital canteen indicated purchasing of healthier snacks increased when a greater proportion of healthier snacks were displayed at the checkout, but there was no impact on less healthy snack purchasing (Van Kleef et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In high-income countries, nutrition-focused interventions in supermarkets are common, including experimental work altering food positioning Huitink et al, 2020;Hyseni et al, 2017) and food labeling (Andreyeva and Luedicke, 2013;Campos et al, 2011;Cecchini and Warin, 2016;Hyseni et al, 2017;Just and Gabrielyan, 2018), both of which show some evidence of impact. However, their applicability to lower-income consumers and rural populations in East Africa is questionable, except for targeting higher-income consumers.…”
Section: Other Information-based Interventionsmentioning
confidence: 99%